Pembuatan Plang Pembatas Dusun dan Pemetaan Potensi Desa sebagai Upaya Peningkatan Fasilitas Desa Pasauran Kab. Serang: Pembuatan Plang Pembatas Dusun dan Pemetaan Potensi Desa sebagai Upaya Peningkatan Fasilitas Desa Pasauran Kab. Serang - Casman Casman; Mutiara Mawaddah; Dini Kamila; Anugrah Wijaya; Yudha Putra; Okti Wildatussilmiah; Maulidya Sabina (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2026)
Pasauran Village is one of the villages located in Cinangka District, Serang Regency, which has coastal regional potential with various resources such as tourism, fisheries, agriculture, plantations, and trade. However, there are still several limitations in supporting village facilities, including the absence of boundary signboards between hamlets and the lack of a village potential map that can serve as an information source for both the community and external parties. This community service activity aims to improve territorial order and provide information regarding village potential through the installation of hamlet boundary signboards and the development of a village potential map in Pasauran Village. The methods used in this activity include field surveys, coordination with village officials, the design of signboards and maps, and the installation of these facilities at designated locations. The results of the activity show that boundary signboards were successfully installed in the seven hamlets of Pasauran Village, making it easier for residents and road users to identify hamlet areas. In addition, the installed village potential map contains information on the locations of public facilities such as health facilities, educational institutions, places of worship, and the village’s economic potentials. The presence of these boundary signboards and the village potential map is expected to enhance administrative order within the village, facilitate access to information, and support more systematic village development planning.